Study of post sunset vertical plasma drift at equatorial F-region using long-term (1990–2003) ionosonde measurements in Indian longitude - Kakad, Bharati; Tiwari, D.; Pant, T.K. (My University, 2012)
Ionosonde measurements from Trivandrum (77°E, 8.5°N, dip 0.5°N) are used to investigate the seasonal and solar flux dependence of peak height, and vertical drift of F layer in post sunset hours. The study reveals that pre- and post-reversal peak vertical drift of F layer increases with solar flux in all seasons. However, the rate of increase is found to be season dependent. Clear difference is observed in the solar flux dependence of peak height and vertical drift for two equinoxes. The post reversal peak westward electric field shows weak (strong) dependence on solar flux during November–February solstice (March–April, September–October equinox).
Keywords: Equatorial ionosphere; F-region vertical drift; Ionosonde